A kind of SLM printing material and preparation method thereof
Through spray drying and heat treatment processes, SLM printing materials with rough surfaces and good dispersion are prepared, which solves the problems of laser reflection and particle agglomeration, and achieves more efficient laser melting and product performance improvement.
Patent Information
- Application Number
- CN202411195977.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-08-29
AI Technical Summary
During the selective laser melt printing process, the smooth surface of the metal powder leads to an increase in laser reflection, requiring higher laser power, and fine particles are prone to agglomeration, affecting dispersion and melting effect.
The spray drying process is used to mix nickel powder, copper powder and iron powder with binder and dispersant to form a spherical precursor powder, and the binder and dispersant are removed by heat treatment to prepare a rough surface and good dispersibility SLM printing material.
By increasing the number of laser reflections, the laser absorption efficiency is improved, the laser ineffective reflection is reduced, and the thermal conduction and thermal conduction paths are improved through the combination of copper powder and iron powder, internal stress accumulation is reduced, and the surface quality and hardness of the product are improved.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of alloy materials and more specifically relates to a SLM printing material and a preparation method thereof. Background Art
[0002] Selective Laser Melting (SLM) technology is an advanced metal additive manufacturing technology. It uses laser as an energy source to scan the metal powder bed layer by layer according to the 3D CAD model to achieve the melting and solidification of metal powder, thereby producing almost fully dense metal parts with good mechanical properties.
[0003] Inconel is an alloy material with excellent oxidation, corrosion and creep resistance at high temperatures. It is usually more expensive than steel, so replacing some Inconel with steel can reduce the cost of parts in terms of cost benefits. This alloy may be used in the energy, oil and gas, and aerospace industries due to its high temperature properties.
[0004] Nickel alloys have great potential for application in SLM (selective laser melting) technology and can be used to manufacture high-performance components with complex geometries. For example, NASA has been trying to manufacture jacketed thrust chambers composed of copper alloys and Inconel by a hybrid method combining SLM and direct energy deposition (DED). This bimetallic component has application prospects in multi-material SLM technology.
[0005] However, SLM printing of nickel alloys also faces some technical challenges, including metallurgical compatibility of materials, matching of thermal expansion coefficients, melting point differences, powder contamination and heat treatment. Solving these problems will promote the development of SLM printing of nickel alloys and expand its advantages and potential in industrial applications. Summary of the invention
[0006] The technical problem to be solved by the present invention is: the inventors have found that for the materials used for selective laser melting printing, in order to improve the fluidity of the raw materials, materials with smooth surfaces are often selected for preparation. However, metal powder materials, after their surfaces are smooth, are prone to cause laser reflection, resulting in the need for higher laser power to promote the melting of the metal powder during the printing process. In addition, in order to fully melt the material, the particles are often prepared very small, but this can easily lead to agglomeration of the particles, making their dispersion a problem. In response to this problem, the present invention provides an SLM printing material and a preparation method thereof.
[0007] The purpose of the present invention is to provide a method for preparing SLM printing materials.
[0008] Another object of the present invention is to provide a SLM printing material.
[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0010] A method for preparing SLM printing materials, the specific preparation steps comprising:
[0011] Nickel powder with a purity greater than 99.5%, copper powder with a purity greater than 99.5%, and iron powder with a purity greater than 99.2% are selected and mixed with a binder, a dispersant and water by ball milling to obtain a mixed slurry;
[0012] spray drying the mixed slurry to obtain spherical precursor powder;
[0013] The obtained spherical precursor powder is heat-treated to remove the binder and the dispersant, and then cooled and discharged to obtain the SLM printing material;
[0014] Wherein, the mass ratio of the nickel powder, the copper powder and the iron powder is (85-88):(8-10):(3-5).
[0015] For the above technical solution, the beneficial effects are:
[0016] The above technical solution firstly uses a spray drying process, a binder and a dispersant to bond metal powder particles for granulation. In this process, the metal powder is bonded by the binder to form spherical particles. In the spherical particles, the metal powder is actually piled up to form a sphere. The surface of this type of sphere is rough because it is piled up between different particles. In this way, the number of reflections of the laser on the surface of the particles can be increased, so that the laser is effectively absorbed and utilized, and the ineffective reflection of the laser is significantly reduced.
[0017] However, the inventors found that for metal particles formed by spray drying, since the forming process of the particles needs to rely on binders and dispersants, these substances will decompose during the subsequent heat treatment process, leaving pores. The accumulation of inherent pores between particles will cause obstacles in the laser melting process. For example, when the temperature is transferred from the surface to the inside, the presence of pores is not conducive to it, which can easily lead to uneven temperature or insufficient melting, and ultimately lead to poor surface of the printed product, or internal stress accumulation leading to serious degradation of product performance; by adding copper powder and iron powder in the above-mentioned mass ratio, this problem can be significantly improved. This is because, first of all, copper powder has a higher thermal conductivity than nickel powder, and there are differences in the absorption of lasers of different wavelengths among copper powder, iron powder and nickel powder. The existence of this difference allows the three powders to more fully utilize laser energy of different bands, thereby ensuring the smooth melting of particles during laser melting and reducing the accumulation of internal stress.
[0018] Furthermore, the D50 of the nickel powder is 650-800nm; the D50 of the copper powder is 200-240nm; and the D50 of the iron powder is 100-120nm.
[0019] The above technical solution has the following beneficial effects:
[0020] Furthermore, by compounding three kinds of metal powders with different particle sizes, on the one hand, a surface with a certain degree of roughness can be formed on the particles, while ensuring that the rough surface is more dense and continuous, avoiding large gaps on the surface; on the other hand, the particle size of copper powder is significantly smaller than that of nickel powder, so that copper powder can fill the accumulation gap formed by nickel powder, thereby forming a fast heat conduction path, and it is also conducive to the rapid and uniform heat dissipation of the printed product, reducing stress accumulation;
[0021] More importantly, since the spray drying process inevitably requires the introduction of organic binders and dispersants, although most of these two types of substances can be decomposed and removed during the heat treatment process, a small amount of carbonaceous components may still remain in the system. The inventors have found that by introducing a certain amount of smaller iron powder into the system, after it is evenly dispersed, it can react with this part of the carbonaceous components during the laser melting process to produce a phase change, forming new phases such as iron carbide, and these phases can also serve as strengthening phases for alloy products, which has a good strengthening effect on the end product.
[0022] Further, the binder is selected from polyvinyl alcohol with an average molecular weight of 130,000 to 150,000;
[0023] Furthermore, the mass fraction of the binder in the mixed slurry is 1.5-2.2%.
[0024] For the above scheme, the beneficial effects are:
[0025] Polyvinyl alcohol with a higher molecular weight is more difficult to decompose, and the viscosity of the formed slurry will increase significantly, which is not conducive to the good dispersion between various metal powders. Therefore, the average molecular weight needs to be controlled below 150,000. If the molecular weight is too low, the bonding force is insufficient.
[0026] Further, the dispersant is selected from any one of Tween 20, Tween 40, Tween 60, Tween 80, Span 20, Span 40, Span 60 or polyethylene glycol;
[0027] Furthermore, the mass fraction of the dispersant in the mixed slurry is 0.6-0.8%.
[0028] Further, the spray drying comprises:
[0029] Spray drying is carried out under the conditions of a feed rate of 80-95 g / min, an inlet air temperature of 138-140° C., an outlet air temperature of 105-110° C., and a main disk speed of the spray dryer of 11500-12000 r / min.
[0030] Further, the heat treatment includes:
[0031] Under argon atmosphere protection conditions, heat to 800°C at a heating rate of 0.6-0.8°C / min, and keep the heat treatment for 40-60 minutes.
[0032] Further, the cooling includes:
[0033] Under argon atmosphere protection conditions, the temperature was rapidly cooled to room temperature at a cooling rate of 8-10°C / min.
[0034] Furthermore, the solid content of the mixed slurry is 72.5-73.2%.
[0035] A SLM printing material is prepared by the above preparation method. DETAILED DESCRIPTION
[0036] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0037] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0038] Example 1
[0039] Nickel powder with a purity greater than 99.5%, copper powder with a purity greater than 99.5%, and iron powder with a purity greater than 99.2%, are selected, mixed with a binder, a dispersant, and water, poured into a ball mill, and zirconium oxide ball milling beads are added at a ball-to-material mass ratio of 1:20, and ball milling is performed for 60 minutes at a rotation speed of 300 r / min and a revolution speed of 400 r / min to obtain a mixed slurry;
[0040] The mass ratio of the nickel powder, the copper powder and the iron powder is 85:8:3;
[0041] The D50 of the nickel powder is 650nm; the D50 of the copper powder is 200nm; the D50 of the iron powder is 100nm;
[0042] By controlling the dosage of the nickel powder, the copper powder and the iron powder, the solid content in the mixed slurry is adjusted to 72.5%;
[0043] The binder is selected from polyvinyl alcohol with an average molecular weight of 130,000;
[0044] Furthermore, the mass fraction of the binder in the mixed slurry is 1.5%;
[0045] The dispersant is selected from Tween 20;
[0046] Furthermore, the mass fraction of the dispersant in the mixed slurry is 0.6%;
[0047] The mixed slurry is conveyed to a spray dryer through a screw pump, and spray-dried at a feed rate of 80 g / min, an air inlet temperature of 138° C., an air outlet temperature of 105° C., and a main disk speed of the spray dryer of 11500 r / min to obtain a spherical precursor powder;
[0048] The obtained spherical precursor powder was transferred into a carbonization furnace, and heated to 800°C at a heating rate of 0.6°C / min under argon atmosphere protection conditions, and heat treated for 40 minutes to remove the binder and dispersant. Then, under argon atmosphere protection conditions, the temperature was quickly cooled to room temperature at a cooling rate of 8°C / min, and the material was discharged to obtain the SLM printing material.
[0049] Example 2
[0050] Nickel powder with a purity greater than 99.5%, copper powder with a purity greater than 99.5%, and iron powder with a purity greater than 99.2%, are selected, mixed with a binder, a dispersant, and water, poured into a ball mill, and zirconium oxide ball milling beads are added at a ball-to-material mass ratio of 1:20, and ball milling is performed for 60 minutes at a rotation speed of 300 r / min and a revolution speed of 400 r / min to obtain a mixed slurry;
[0051] The mass ratio of the nickel powder, the copper powder and the iron powder is 86:9:4;
[0052] The D50 of the nickel powder is 720nm; the D50 of the copper powder is 220nm; the D50 of the iron powder is 110nm;
[0053] By controlling the dosage of the nickel powder, the copper powder and the iron powder, the solid content in the mixed slurry is adjusted to 72.9%;
[0054] The binder is selected from polyvinyl alcohol with an average molecular weight of 140,000;
[0055] Furthermore, the mass fraction of the binder in the mixed slurry is 1.9%;
[0056] The dispersant is selected from Tween 60;
[0057] Furthermore, the mass fraction of the dispersant in the mixed slurry is 0.7%;
[0058] The mixed slurry is conveyed to a spray dryer through a screw pump, and spray-dried at a feed rate of 88 g / min, an air inlet temperature of 139° C., an air outlet temperature of 108° C., and a main disk speed of the spray dryer of 11800 r / min to obtain a spherical precursor powder;
[0059] The obtained spherical precursor powder was transferred into a carbonization furnace, and heated to 800°C at a heating rate of 0.7°C / min under argon atmosphere protection conditions, and heat treated for 50 minutes to remove the binder and dispersant. Then, under argon atmosphere protection conditions, the temperature was quickly cooled to room temperature at a cooling rate of 9°C / min, and the material was discharged to obtain the SLM printing material.
[0060] Example 3
[0061] Nickel powder with a purity greater than 99.5%, copper powder with a purity greater than 99.5%, and iron powder with a purity greater than 99.2%, are selected, mixed with a binder, a dispersant, and water, poured into a ball mill, and zirconium oxide ball milling beads are added at a ball-to-material mass ratio of 1:20, and ball milling is performed for 60 minutes at a rotation speed of 300 r / min and a revolution speed of 400 r / min to obtain a mixed slurry;
[0062] The mass ratio of the nickel powder, the copper powder and the iron powder is 88:10:5;
[0063] The D50 of the nickel powder is 800nm; the D50 of the copper powder is 240nm; the D50 of the iron powder is 120nm;
[0064] By controlling the dosage of the nickel powder, the copper powder and the iron powder, the solid content in the mixed slurry is adjusted to be 73.2%;
[0065] The binder is selected from polyvinyl alcohol with an average molecular weight of 150,000;
[0066] Furthermore, the mass fraction of the binder in the mixed slurry is 2.2%;
[0067] The dispersant is selected from polyethylene glycol;
[0068] Furthermore, the mass fraction of the dispersant in the mixed slurry is 0.6-0.8%;
[0069] The mixed slurry is conveyed to a spray dryer through a screw pump, and spray-dried under the conditions of a feed rate of 95 g / min, an air inlet temperature of 140° C., an air outlet temperature of 110° C., and a main disk speed of the spray dryer of 12000 r / min to obtain a spherical precursor powder;
[0070] The obtained spherical precursor powder was transferred into a carbonization furnace, and heated to 800°C at a heating rate of 0.8°C / min under argon atmosphere protection conditions, and heat treated for 60 minutes to remove the binder and dispersant. Then, under argon atmosphere protection conditions, the temperature was quickly cooled to room temperature at a cooling rate of 10°C / min, and the material was discharged to obtain the SLM printing material.
[0071] Example 4
[0072] Compared with Example 1, this embodiment is different in that:
[0073] The D50 of the copper powder is 640 nm, and the other conditions remain unchanged.
[0074] Example 5
[0075] Compared with Example 1, this embodiment is different in that:
[0076] The D50 of the copper powder is 640 nm, and the D50 of the iron powder is 645 nm, and the other conditions remain unchanged.
[0077] Comparative Example 1
[0078] The difference between this comparative example and Example 1 is that no copper powder is added, and other conditions remain unchanged.
[0079] Comparative Example 2
[0080] The difference between this comparative example and Example 1 is that no iron powder is added, and the other conditions remain unchanged.
[0081] Comparative Example 3
[0082] The difference between this comparative example and Example 1 is that neither iron powder nor copper powder is added, and the other conditions remain unchanged.
[0083] The performance tests were performed on the products obtained in the above embodiments or comparative examples. The specific test methods and test results are as follows:
[0084] The surface roughness of the SLM printed materials obtained in the above embodiments or comparative examples was measured using a LEXT OLS400 laser confocal microscope; the detailed test results are shown in Table 1;
[0085] EOSINT M280 metal laser rapid prototyping machine and Yb-fibre solid laser were used as equipment for sample preparation;
[0086] On the powder bed, the motion trajectory of the laser beam is controlled to accumulate layer by layer to obtain a sample of a certain shape to be tested, where the laser power is 220 W, the scanning rate is 950 mm / s, the layer thickness is 25 μm, the scanning spacing is 85 μm, 316L stainless steel is used as the substrate, the preheating temperature is set to 80 °C, and the sample size is 8 mm × 8 mm × 5 mm.
[0087] The hardness of the printed part was measured using an FM-700 digital microhardness tester with a load of 49 N and a holding time of 15 s. The detailed test results are shown in Table 1.
[0088] Table 1: Product performance test results
[0089] Surface roughness <![CDATA[Hardness (kg / mm 2 )]]> Example 1 0.344 215.1 Example 2 0.342 214.9 Example 3 0.345 215.4 Example 4 0.349 209.8 Example 5 0.352 204.5 Comparative Example 1 0.350 201.1 Comparative Example 2 0.349 198.9 Comparative Example 3 0.359 180.1
[0090] Compared with Example 1, the increase in copper powder D50 in Example 4 leads to an increase in large powder constituting the particles, and therefore, an increase in surface roughness. Although the laser absorption is better, the dispersion of the copper powder deteriorates, and the pores on the surface or inside increase or increase, resulting in the hardness of the final product not being improved but decreasing. The relevant mechanism of Example 5 is similar to this. In Comparative Examples 1-3, due to the lack of addition of small-particle powder, the relative content of large-particle powder increases, and the roughness also increases. However, due to the lack of the effect of copper powder and iron powder, the hardness decreases more significantly.
[0091] It can be seen from the test results in Table 1 that the product obtained by the present invention has a certain surface roughness, and at the same time, the printed product has a higher hardness.
[0092] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing SLM printing materials, characterized in that: The specific preparation steps include: Nickel powder with a purity greater than 99.5%, copper powder with a purity greater than 99.5%, and iron powder with a purity greater than 99.2% are selected and mixed with a binder, a dispersant and water by ball milling to obtain a mixed slurry; spray drying the mixed slurry to obtain spherical precursor powder; The obtained spherical precursor powder is heat-treated to remove the binder and the dispersant, and then cooled and discharged to obtain the SLM printing material; Wherein, the mass ratio of the nickel powder, the copper powder and the iron powder is (85-88): (8-10): (3-5); The D50 of the nickel powder is 650-800nm; the D50 of the copper powder is 200-240nm; the D50 of the iron powder is 100-120nm; The binder is selected from polyvinyl alcohol with an average molecular weight of 130,000 to 150,000; Moreover, the mass fraction of the binder in the mixed slurry is 1.5-2.2%.
2. The method for preparing a SLM printing material according to claim 1, characterized in that: The dispersant is selected from any one of Tween 20, Tween 40, Tween 60, Tween 80, Span 20, Span 40, Span 60 or polyethylene glycol; Moreover, the mass fraction of the dispersant in the mixed slurry is 0.6-0.8%.
3. The method for preparing a SLM printing material according to claim 1, characterized in that: The spray drying comprises: Spray drying is carried out under the conditions of a feed rate of 80-95 g / min, an inlet air temperature of 138-140° C., an outlet air temperature of 105-110° C., and a main disk speed of the spray dryer of 11500-12000 r / min.
4. The method for preparing a SLM printing material according to claim 1, characterized in that: The heat treatment comprises: Under argon atmosphere protection conditions, heat to 800°C at a heating rate of 0.6-0.8°C / min, and keep the heat treatment for 40-60 minutes.
5. The method for preparing a SLM printing material according to claim 4, characterized in that: The cooling comprises: Under argon atmosphere protection conditions, the temperature was rapidly cooled to room temperature at a cooling rate of 8-10°C / min.
6. The method for preparing a SLM printing material according to claim 1, characterized in that: The solid content of the mixed slurry is 72.5-73.2%.
7. A SLM printing material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Powder material to be used in powder lamination shaping and powder lamination shaping method using same
CN106457668A
Method for preparing powder metallurgy copper-based friction material through adhesion process
CN107326205A